Estresse pós-traumático e tratamento com cetamina em ratos Wistar : análise comportamental, histofisiológica, bioquímica e neurometabólica - Saur, Lisiani (2017)
Post-traumatic stress disorder (PTSD) is a neuropsychiatric condition related to exposure to a traumatic event. It is clinically characterized by several debilitating symptoms including frequent re-experiencing of the traumatic event, avoidance bahavior, hypervigilance, and cognitive and mood changes among others. Not all individuals exposed to severe traumatic experiences develop PTSD. This psychopathology affects a vulnerable subpopulation of individuals confronted with a stressful experience that exceeds their capacity to cope. In this sense, it has been argued that PTSD can be considered a fear-related disorder. Thus, the brain regions most widely studied in this psychopathology are the prefrontal cortex, the hippocampus and the amygdala, because they are related to the storage and consolidation of new memories including emotional memories, such as fear and anger. Due to the complex clinical presentation of PTSD and its very variable symptoms, it is considered a condition to treat. Ketamine is an NMDA receptor antagonist that has shown promising effects in the treatment of depression. However, because it produces dissociative and psychotic effects, there is a concern this drug might be related with increased PTSD symptoms. One of the most widely used animal models to mimic the behavioral and neurochemical changes of PTSD is the inescapable footshock. In the first part of this study, we observed significant behavioral and histological changes caused by exposure to footshock. Animals with PTSD exhibited longer freezing bouts when re-exposed to the same aversive context, as well as increased pellet production. In addition, important changes were observed in astrocytes from the hippocampal CA1 region of these animals, such as decreased astrocytic density, ramification and fewer primary processes. Furthermore, the polarity of the astrocytes was also changed when compared to control animals. In the second part of this study, we analyzed the effects of ketamine on this animal model. Since not all animals have the same response during the re-exposure to aversive environment, that is, the animals have individual differences in their susceptibility to traumatic stress, we decided to separate the animals with PTSD into two groups: those with an extreme behavioral response (EBR) and those with a minimal behavioral response (MBR). Furthermore, the glucose metabolism and the BDNF levels in the frontal cortex, hippocampus and amygdala were analyzed 8 and 9 days after PTSD induction, respectively. BDNF levels were analyzed through biochemical assays and glucose metabolism was analyzed by 18F-FDG-microPET, which measures the glucose uptake in tissues, in other words, the metabolic demand. We observed that animals with PTSD classified as EBR showed an increase in freezing behavior and the treatment with ketamine worsened that behavioral response, that is, the ketamine worsened the PTSD symptoms. However, no changes were observed in BDNF levels or glucose metabolism. These results demonstrate that footshock as an animal model of PTSD induced significant behavioral and astrocytic alterations. We also observed that ketamine worsened the PTSD symptoms and that, as is the case with humans, not all individuals that are exposed to a traumatic stress develop PTSD. However, this animal model does not seem to be related to long-term changes in BDNF levels or glucose metabolism.